Rancang Bangun dan Uji Eksperimental Performa Burner Biomassa Berbahan Bakar Limbah Nyamplung (Calophyllum Inophyllum) dan Pelet Kayu - Syamsiro, Mochamad; Anwar, Nurcaya Putra; Ika, Siti Rochmah; Mulyono, Agus; Laksana, Feri Febria; Rina, Fadmi (LPPM Universitas Mataram, 2025)
As a tropical country, Indonesia has abundant biomass potential because plants grow all year. Among the several types of biomass, nyamplung kernel cake (NKC) has a high potential for use as an energy source. The goal of this research was to develop a biomass burner and evaluate its performance using NKC and wood pellets (WP) as comparisons. The burner performance test is designed to investigate the effect of air mass flow rate on combustion flame, heat release rate, and thermal efficiency for both types of biomass. The thermal efficiency of the burner was calculated using the water boiling test (WBT). The results revealed that using NKC resulted in a longer combustion flame at air flow rates of 146 and 219 g/s. The higher the air flow rate, the longer the flame. The combustion of NKC and WP produced the longest flame, measuring 80 cm with an air mass flow rate of 290 g/s. The experiment also demonstrated that WP produced a higher temperature than NKC. The highest combustion temperature was produced by WP, reaching 818.1Â°C with an air mass flow rate of 290 g/s. From the two types of biomass evaluated, WP combustion produced more heat than NKC. The highest heat release rate of 35.46 kW was achieved with an air mass flow rate of 290 g/s. The burning of NKC resulted in the maximum thermal efficiency, 30.35% at an air mass flow rate of 219 g/.